Income and use of money in the peasant economy: contributions to rural development psychology from a case study - Landini, Fernando Pablo (2011)
Rural development processes taking place in peasant communities constitute an area of interest for community psychology, however, it is clear that this subdiscipline has made limited contributions to the comprehension of the psychosocial factors involved. This article considers that the peasant economic rationality differs profoundly from that proposed by market capitalism and that a better comprehension of its principles and priorities would be of vital importance to improve current initiatives dedicated to rural development. Thus, an investigation was conducted in the northeast of Argentina in an effort to understand the practices and representations tied to the use of money in peasant communities. The research arrived to the conclusion that the peasants, due to the fact that they live in an economy where scarcity is the norm, have resources and personal abilities to deal with contexts characterized by economic restrictions, but no with those of relative abundance.